Determination The Effective Dose of Sodium Thiosulfate in Adult Rats Treated with Nicotine - Altamemi, Zena Shakir; Al-Okaily , Baraa Najim (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Sodium thiosulfate (STS) is a possible therapeutic candidate molecule in a range of diseases and drug-induced toxicities due to its antioxidant, anti-inflammatory, and anti-apoptotic capabilities. The current study aimed to find the effective dose of STS in adult male rats given nicotine by evaluating serum MDA and blood partial pressure of oxygen (PO2) levels. Thirty-six adult male Wistar rats, Rattus norvegicus (weighing 190–220 g) with an age of 3–3.5 months, were chosen randomly and separated into six equal groups, administered for 28 days. Animals in the control group were administered an intraperitoneal (i.p.) injection of normal saline, while those in groups 1, 2, 3, 4, and 5 received repeated doses of an i.p. nicotine injection of 1.5 mg/kg b.w. One hour later, they were i.p. injected with 150, 250, 350, 450, and 550 mg/kg b.w. of STS, respectively. Both medications continued to be given for a period of 28 days. At the end of the experiment, serum malondialdehyde (MDA) and PO2 were measured. Results showed a negative relationship between blood PO2 concentration and five successive doses of sodium thiosulfate, but a positive linear relationship among successive doses of sodium thiosulfate on serum MDA concentration was observed. The estimated amount of sodium thiosulfate that caused a considerable decrease in serum MDA levels and a rise in blood PO2 was found to be 450 mg/kg bw. The current study’s findings show that different doses of sodium thiosulfate can significantly reduce the harmful effects of nicotine exposure by reducing the formation of oxidative stress and the detrimental effects on respiratory function, which are characterized by an increase in blood PO2 levels.